The Role of the Pangandaran Regency DPRD in Supervising the Development of Regional Government Infrastructure - Bunga Aulya Zahra; Sendi Setiawan; Tesya Meilani Adiningsih; Arie Budiawan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Pangandaran Regency is trying to improve the quality and capacity of infrastructure, this can be seen from the still less than optimal quality of infrastructure services in Pangandaran Regency. Therefore, the Pangandaran Regency DPRD as an element of the Regional Government must be able to carry out its role as a representative institution of the people in the region so that infrastructure development can be in accordance with the plan, correct errors in the field and be able to perfect development programs. This study aims to determine the role of the DPRD in supervising infrastructure development in Pangandaran Regency. Descriptive qualitative research methods using data collection techniques in the form of interviews, documentation and literature studies. Data analysis and interpretation through the stages of data collection, reduction, display, and conclusion. Research quality using triangulation of source data.The results of the study indicate that the stages and schemes of DPRD supervision are quite effective in correcting errors in the field and also improving infrastructure development programs; transparent DPRD relations and having a commitment to realizing targets have an impact on achieving development program targets that are all achieved; there is a relationship between DPRD interest and the infrastructure development supervision process; the community is involved in the planning, implementation and monitoring stages of development and the participation of tender participants. The conclusion is that the role of DPRD in supervising infrastructure development in Pangandaran Regency is going well, although there are driving and inhibiting factors in implementing supervision